Validation of a preliminary competency assessment scale for Malaysian graphic design graduates - Wong, Shaw-Chiang; Zaffwan Idris, Muhammad (Journal of Graphic Engineering and Design, 2022)
The criteria for measuring the competency levels of graphic design (GD) graduates have continuously been shaped by the changing context of practice. However, previous studies provide little evidence on the existence of an effective competency assessment scale for GD graduates. The purpose of the study is to evaluate the psychometric properties of a preliminary competency assessment scale for GD graduates in Malaysia. 207 final year GD degree students in Malaysia were sampled to validate the scale. The data was analysed using exploratory factor analysis and Cronbach’s reliability test. The results suggested that the preliminary scale consists of 12 constructs and 59 items under five competency dimensions. All 12 constructs yielded high internal consistency values, ranging between .723 and .914. Theoretically, the validated scale contributed to a new body of knowledge to the competency assessment of GD graduates in Malaysia. Practically, the findings provided relevant stakeholders with prescribed standards of performance and appropriate tools to assess the competency levels of new entrants to the GD profession. Article history: Received (December 21, 2021); Revised (May 15, 2022); Accepted (June 7, 2022); Published online (September 1, 2022)